Beefing IT Up for Your Investor? Engagement with Open Source Communities, Innovation, and Startup Funding: Evidence from GitHub - Conti, Annamaria; Peukert, Christian; Roche, Maria (Organization Science, 2025)
We study the engagement of nascent firms with open source communities and its implications for innovation and attracting funding. To do so, we link data on 160,065 U.S. startups from Crunchbase to their activities on the open source software development platform GitHub. In a matched sample of firms with and without GitHub activities, difference-in-differences models reveal a substantial increase in the likelihood of being funded after early stage startups engage with open source communities on GitHub. This relationship is weaker for firms that employ GitHub for internal development only. Startups developing novel technologies tend to benefit more from engaging with open source communities, unlike those in highly competitive environments. This heterogeneity highlights a potential trade-off between engaging with open source communities and appropriability. To provide insight regarding mechanisms, we classify startups’ technology use-cases on GitHub using machine learning and exploit data on product launches. Our results from these additional analyses support the notion that one important channel potentially driving our findings is the access to external knowledge for technology development provided by open source communities. Engaging with these communities may thereby aid startups in innovating and creating a (minimum) viable product. Funding: A. Conti and C. Peukert received financial support from the Swiss National Science Foundation [Project IDs 100013_188998 and 100013_197807]. M. Roche received financial support from the Harvard Business School Division of Research and Faculty Development. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2023.18348 .